2022
DOI: 10.1136/gutjnl-2020-323897
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of non-curative endoscopic submucosal dissection for early colorectal cancer

Abstract: ObjectiveEndoscopic submucosal dissection (ESD) in a curative intent for submucosa-invasive early (T1) colorectal cancers (T1-CRCs) often leads to subsequent surgical resection in case of histologic parameters indicating higher risk of nodal involvement. In some cases, however, the expected benefit may be offset by the surgical risks, suggesting a more conservative approach.DesignRetrospective analysis of consecutive patients with T1-CRC who underwent ESD at 13 centres ending inclusion in 2019 (n=3373). Cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Endoscopic resection has emerged as an effective method to remove some early-stage CRCs before open surgery. 71 Unnecessary surgical resection may pose additional risks. However, 8% of patients with T1 and 18.5% of patients with T2 CRCs have lymph node metastases (LNM), which is a contraindication to endoscopic resection.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Endoscopic resection has emerged as an effective method to remove some early-stage CRCs before open surgery. 71 Unnecessary surgical resection may pose additional risks. However, 8% of patients with T1 and 18.5% of patients with T2 CRCs have lymph node metastases (LNM), which is a contraindication to endoscopic resection.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…ESD may, however, have a problem with the vertical resection margin in cases of deep submucosal invasion. Thus, a recent Western retrospective multicenter study with 207 colorectal ESDs reported a positive vertical margin in 57% of the cases, and a positive vertical margin was the most frequent reason for a 'noncurative' endoscopic resection [48]. A possible caveat regarding the vertical resection margin also comes from a small pilot study comparing colorectal specimens obtained by EMR (n = 6 benign lesions) versus ESD (n = 6, with one case of submucosal invasive cancer) and quite unexpectedly showed a better preserved and thicker submucosal layer in EMR specimens [49,50].…”
Section: Esdmentioning
confidence: 99%
“…However, such mere classification should not automatically result in the decision for surgery. For instance, an apparently noncurative resection due to a high-risk pathologic findings may be sufficient in a patient with a high risk of surgery-related mortality, 31,43 while a low-risk lesion may still not exclude surgery in a very young and fit patient. Thus, a multidisciplinary reassessment is required after the pathology assessment, and it may require the presence of other experts (eg oncologist, radiologist).…”
Section: Pathologic and Multidisciplinary Assessmentmentioning
confidence: 99%